A cross-sectional study to assess the performance of undergraduates on critical evaluation of a drug promotional literature and its correlation with their knowledge on research methodology - L. N. Babu; B. Maharani; Prakash Mathiyalagen (Journal of Current Research in Scientific Medicine, 2025)
Background: Critical appraisal of drug promotional literature (DPL) exercise was included in the undergraduate (UG) curriculum to entrain them to perform a critical appraisal individually at the end of the exercise. The word “critical” denotes in-depth analysis, especially about the research methodology (RM)/scientific component. However, UG curriculum does not impart RM at the 2nd-year MBBS (Bachelor of Medicine and Bachelor of surgery) level. Hence, knowledge acquired at the end of the exercise is doubtful. This study addresses the noncoherence. Hence, the objectives of the current study were to assess the performance of UGs on critical evaluation of DPL using the checklist similar to the World Health Organization (WHO) checklist and to assess the UG’s knowledge on RM and basic pharmacology (BP) and to correlate it with their performance of critical evaluation of DPL. Materials and Methods: A validated checklist similar to the WHO checklist for DPL was devised (the addition was scientific component-a prerequisite for critical evaluation). A formal training session was conducted and then a new DPL was given for assessment, to a score of 10 followed by assessment on RM (25 multiple-choice questions [MCQs] and BP (10 MCQs). The performance of DPL was compared with the performance on RM and BP using means and proportions as, % of students scoring >70%, >50% and average class score % in all three tests. Performance coherence was also assessed using Pearson’s correlation. Results: Students’ performance of DPL vs. RM with ≥70% was 99.2% vs. 23.9%; ≥50% was 100% vs. 65.2%; and the average class score was 89.63% vs. 59.41%. P < 0.001 in all comparisons was found. Pearson’s correlate for comparison between DPL and RM was, r = −0.086. Conclusion: The poor performance of undergraduates on Research Methodology compared to drug promotional literature is due to lack of knowledge on research methodology among II year undergraduates. Hence, DPL exercise will be fruitful to undergraduates when it is provided with the training session on research methodology as it is a important component required for the critical evaluation of a drug promotional material.